Fatores genéticos, biofísicos e de manejo que influenciam na concentração de proteína em lavouras de soja no Brasil - Arce, María Sol Zelaya (2024)
Context: The demand for high-quality soybeans is expected to increase. The composition of soybeans can vary due to genetics, biophysical factors, and management practices. In particular, studies on protein content are still in their infancy in the country. Objectives: Our objectives were to quantify the genetic effects on seed protein concentration and to identify the biophysical and management factors that influence seed protein concentration in the different soybean production systems in Brazil. Methods: We collected soybean samples and data of location and crop management through surveys in 194 soybean producers’ fields in two growing seasons (2018/2019; 2022/2023) across eleven states in Brazil. Seed protein was determined by Kjeldahl method. We used regression trees, random forest regressions and comparisons between high and low protein fields to identify the main causes of variation in soybean seed protein concentrations. Results: Fields with the highest protein concentration were observed in older cultivars released in (2011), at lower yields (3082 kg ha-1), late sowing (DOY 313), higher temperatures (25.6 °C-1) and a lower photothermal coefficient (0.79 MJ m-2 d-1 °C-1). Conversely, low protein concentration was observed in fields with higher yields (4220 kg ha-1), early sowing (DOY 302), lower temperatures (24.8°C-1) and a higher photothermal coefficient (0.84 MJ m-2 d-1 °C-1) and newer cultivars released in (2016). The regression tree and random forest explained 58% of the protein variability. Relative to this explained variation, cultivar (39%) was the most important factor, following by latitude (12%) and sowing date (7%). Rainfed environments had higher seed protein concentration compared to irrigated fields. Conclusion: Cultivar was the most important factor affecting soybean seed protein concentration. Sowing date was the management practice with higher variation in protein concentration. Cultivar release year, breeding companies, latitude, temperature, photothermal coefficient and water supply also affected the final concentration of soybean seed protein. Significance: Our study provides useful information for guiding investments and apply strategies for producers, decision-making of processor and exporters of the entire soybean complex produced in Brazil to attend high quality demand.